Distribution of malaria vectors and incidence of vivax malaria at Korean army installations near the demilitarized zone, Republic of Korea. (December 2016) - Chang, Kyu; Yoo, Dae-Hyun; Ju, Young; Lee, Wook; Roh, Jong; Kim, Heung-Chul; Klein, Terry; Shin, E-Hyun
Abstract Background As a result of the reintroduction of malaria in the Republic of Korea (ROK) in 1993 and the threat to military and civilian populations, the Korea Military National Defense (MND) increased emphasis on vector control in 2012 at ROK Army (ROKA) installations located near the DMZ, while decreasing chemoprophylaxis, fearing potential drug resistance. Mosquito surveillance demonstrated a need for continuous monitoring of disease patterns among ROKA soldiers and vector malaria infection rates to ensure positive outcomes. Methods Anopheles spp. were collected from May–October at three ROKA installations in three locations near the DMZ. Each of the areas included one installation <2 km and two installations 11–12 km from the DMZ in Paju and Yeoncheon counties, Gyeonggi Province.Anopheles spp. were identified by polymerase chain reaction (PCR) techniques and then assayed for the presence of vivax malaria sporozoites. The ROK MND reported vivax malaria patients monthly to Korea Centers for Disease Control and Prevention. Correlations for the incidence ofPlasmodium vivax patients and infectedAnopheles species were analysed using the Wilcoxon rank sum test, Pearson correlation test and liner regression analysis. Results A total of 4282Anopheles spp. were collected.Anopheles kleini (69.5 %) was the most commonly collected, followed byAnopheles pullus (17.3 %), Anopheles belenrae (4.5 %), Anopheles sineroides (4.2 %), Anopheles sinensis sensu stricto (2.7 %), andAnopheles lesteri (1.9 %). Overall, 21 malaria patients were reported by the ROK MND. The monthly incidence of the malaria patients correlated with the monthly number ofPlasmodium vivax sporozoite positiveAnopheles spp. The monthly numbers ofAn. kleini demonstrated the highest correlations to the numbers of ROKA malaria patients throughout the mosquito season (P < 0.01).Anopheles spp. positive forP. vivax and malaria patients at ROKA installations located <2 km from the DMZ were higher than for ROKA installations located 11–12 km from DMZ. Conclusion The number ofAnopheles spp. positive forP. vivax sporozoites correlated with the monthly number of malaria cases and exposure of ROKA soldiers from May–October toP. vivax malaria infections. Malaria vector surveillance and vector control is warranted as part of an effective malaria management program at ROKA installations located near DMZ.